MODEL OF DISTRIBUTION PLAN OF EMPTY CARS FOR LOADING - Kukushkina, I. M. (Science and Transport Progress, 2003)
An economic and mathematical model of empty carflow rational regulation has been offered, with account of expenditures, related to the time losses by cars and the freight in a pre-loading demurrage, and also the costs of the cars moving from the points of loading to those of unloading.